Selected thermal waste treatment plants in europe - case study - Olejnik, Dorota; Krupa, Marcin (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The functioning of societies involves the generation of large amounts of municipal waste. This study analyses the amounts of pollutants emitted during waste incineration at selected waste incineration plants in 2022. Four plants were analyzed, including three with the highest waste processing efficiency (Copenhagen, Poznan and Kraków) and one with the lowest efficiency (Konin). The choice of the factory in Copenhagen was also dictated by its strategic location in the city center. Analysing the emissions from the selected plants it can be concluded that environmental safety was maintained and none of the plants exceeded the permissible emissions value.
Keywords: thermal waste treatment plant; incineration; permissible value; pollutant emission